Understanding Public Transport Loyalty: The Roles of Service Quality, Satisfaction, and Perceived Value - Arif Fakhrudin; Kifni Yudianto; Maria Valeria Roellyanti (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
Public transportation plays a crucial role in promoting sustainable urban mobility and reducing reliance on private vehicles. However, many public transport systems face challenges in maintaining long-term passenger loyalty. Understanding the determinants of passenger loyalty is therefore essential for transportation providers and policymakers seeking to enhance service performance and increase ridership. This study aims to examine the relationships among service quality, perceived value, passenger satisfaction, and passenger loyalty in public transportation services. A quantitative research approach was employed using a structured survey distributed to public transportation users. Data were collected from 200 respondents and analysed using Structural Equation Modelling (SEM) to test the proposed hypotheses and examine the relationships among the constructs. The measurement model was evaluated to ensure reliability and validity before conducting structural model analysis. The results reveal that service quality significantly influences both perceived value and passenger satisfaction. Furthermore, perceived value has a positive effect on passenger satisfaction and passenger loyalty. The findings also indicate that passenger satisfaction plays a critical role in enhancing passenger loyalty toward public transportation services. These results highlight the importance of delivering reliable, safe, and comfortable transportation services in order to improve passenger perceptions and encourage continued usage. This study contributes to the literature on transportation service management by providing empirical evidence on the mechanisms through which service quality and perceived value influence passenger loyalty. The findings also offer practical implications for transportation providers and policymakers seeking to improve service quality, enhance passenger satisfaction, and promote sustainable public transport usage.